MANGANESE-CHROMIUM ISOTOPE SYSTEMATICS OF ENSTATITE METEORITES - Shukolyukov A.; Lugmair G.W. (My University, 2004)
We present results of a study of the 53Mn-53Cr isotope systematics in the enstatite chondrites and achondrites (aubrites). The goal of this study was to explore the capabilities of this isotope system to obtain chronological information on these important classes of meteorites and to investigate the original distribution in the inner solar system of the short-lived radionuclide 53Mn. Our earlier work (Lugmair and Shukolyukov, 1998; Shukolyukov and Lugmair, 2000a) has shown that the asteroid belt bodies are characterized by essentially the same initial 53Mn abundance. However, we have found the presence of a gradient in the abundance of the radiogenic 53Cr between the earth-moon system, Mars, and the asteroid Vesta. If this gradient is considered as a function of the heliocentric distance a linear radial dependence is indicated. This can be explained either by an early, volatility controlled Mn/Cr fractionation in the nebula or by an original radially heterogeneous distribution of 53Mn. The enstatite chondrites are suggested to form in the inner zones of the solar nebula, much closer to the Sun than the ordinary chondrites. Therefore, their investigation may be an important test on the hypothesis on a radial heterogeneity in the initial 53Mn.